2020
DOI: 10.1056/nejmsa2011686
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization and Mortality among Black Patients and White Patients with Covid-19

Abstract: BACKGROUNDMany reports on coronavirus disease 2019 have highlighted age-and sex-related differences in health outcomes. More information is needed about racial and ethnic differences in outcomes from Covid-19. METHODSIn this retrospective cohort study, we analyzed data from patients seen within an integrated-delivery health system (Ochsner Health) in Louisiana between March 1 and April 11, 2020, who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, the virus that causes Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

189
1,544
29
49

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,571 publications
(1,811 citation statements)
references
References 19 publications
189
1,544
29
49
Order By: Relevance
“…This is aligned with many studies both in pregnant and nonpregnant populations that have demonstrated significant racial disparities in incidence and outcomes. 13,20,21 A multitude of factors, including health care access, social determinants of health, and underlying comorbidities may underlie these disparities in COVID-19 spread, incidence, and outcomes in non-White populations. The etiology of these demographic findings should be interrogated seriously with both qualitative and quantitative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This is aligned with many studies both in pregnant and nonpregnant populations that have demonstrated significant racial disparities in incidence and outcomes. 13,20,21 A multitude of factors, including health care access, social determinants of health, and underlying comorbidities may underlie these disparities in COVID-19 spread, incidence, and outcomes in non-White populations. The etiology of these demographic findings should be interrogated seriously with both qualitative and quantitative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…18,28,31,39,[41][42][43]46,47,50,52,53,57,61,63,64,[69][70][71][72][73] The immunopathogenesis of SARS-CoV-2 infection is typified by an aggressive inflammatory response, 74 and accordingly, elevated inflammatory markers are common. 18,28,[41][42][43]46,47,50,52,61,63,64,[69][70][71][72] Lymphopaenia and an increased neutrophil to lymphocyte ratio can occur in many patients with SARS-CoV-2 infection. 37,52,74 Close monitoring of inflammatory markers and serum cytokine and chemokine levels is crucial to the optimal management of COVID-19 patients, 37,75 as severe SARS-CoV-2 infection can result in the manifestation of a cytokine storm syndrome.…”
Section: Symptoms Associated With Covid-19mentioning
confidence: 99%
“…International mehren sich aktuell die Hinweise, die auf eine sozial ungleiche Verteilung des Risikos für eine Infektion mit SARS-CoV-2 und für schwere Verläufe von COVID-19 in einigen Ländern hindeuten [4]. Aus den USA liegen erste Berichte vor, dass Afroamerikanerinnen und Afroamerikaner sowohl bei den bestätigten Fällen als auch bei Hospitalisierungen und Todesfällen aufgrund von COVID-19 überrepräsentiert sind [5][6][7]. Aus New York City, einem der Epizentren des Ausbruchs in den USA, berichten die lokalen Gesundheitsbehörden eine doppelt so hohe altersadjustierte Sterberate für Afroamerikanerinnen und Afroamerikaner sowie eine um 50 % erhöhte Sterberate in der Bevölkerung mit hispanobzw.…”
Section: Soziale Ungleichheit In Der Frühen Covid-19-pandemieunclassified
“…Auch aus Großbritannien gibt es Berichte, dass People of Color (POC) häufiger schwere klinische Verläufe zeigen [9]. Ein Teil dieser ethnischen Ungleichheiten im COVID-19-Sterberisiko dürfte auf Unterschiede im sozioökonomischen Status zurückgehen [7,10,11], auch wenn die komplexen Muster gesundheitlicher Ungleichheit nach Ethnizität nicht allein auf diese reduzierbar sind [11]. Zu den Mustern sozioökonomischer Ungleichheit im COVID-19-Geschehen liegen bisher jedoch nur wenige und meist ökologische Analysen vor.…”
Section: Soziale Ungleichheit In Der Frühen Covid-19-pandemieunclassified